After Annie : a novel [compact disc, unabridged] - Quindlen, Anna (Random House, 2024)
When Annie Brown dies suddenly, her husband, her four young children and her closest friend are left to struggle without the woman who centered their lives. Bill Brown finds himself overwhelmed, and Annie's best friend Annemarie is lost to old bad habits without Annie's support. It is Annie's daughter, Ali, forced to try to care for her younger brothers and even her father, who manages to maintain some semblance of their former lives for them all, and who confronts the complicated truths of adulthood. Yet over the course of the next year, while Annie looms large in their memories, all three are able to grow, to change, even to become stronger and more sure of themselves. The enduring power Annie gave to those who loved her is the power to love, and to go on without her.